Association of Surgeon Representation on NIH Study Sections With Receipt of Funding by Surgeon-scientists. Issue 6 (June 2021) - Lewit, Ruth A.; Black, Caitlin M.; Camp, Lauren; Brott, Nathan; Cottrell, J. Macy; Herman, Timothy; Holden, Kylie W.; Matthews, Lynley; Schneider, Elizabeth; Goldstein, Allan M.; Matthews, Jeffrey B.; Emamaullee, Juliet; et al.
Abstract : Objective: Our goal was to evaluate the relationship between surgeon representation on NIH study sections and success in grant funding. Summary of Background Data: NIH funding for surgeon-scientists is declining. Prior work has called for increased surgeon participation in the grant review process as a strategy to increase receipt of funding by surgeon-scientists. Methods: A retrospective review of surgeon (primary department: General, Urology, Orthopedic, Ophthalmology, Otolaryngology, Neurosurgery) representation on NIH study sections and receipt of funding was performed using NIH Research Portfolio Online Reporting Tools Expenditures and Results (RePORTER) and 2019 Blue Ridge Institute for Medical Research data. NIH chartered study section panels and ad hoc reviewers for each 2019 review date were also obtained. Results: In 2019, 9239 individuals reviewed in at least 1 of the 168 study sections [190 (2.1%) surgeons, 64 (0.7%) standing members, 126 (1.4%) ad-hoc]. Most surgeons on study sections were male (65%) professors (63%). Surgeons most commonly served on bioengineering, technology, and surgical sciences (29.6% surgeons), diseases and pathophysiology of the visual system (28.3%), and surgery, anesthesiology and trauma (21%). In 2019, 773 surgeons received 1235 NIH grants (>$580 M) out of a total of 55, 012 awards (2.2%). Funded surgeons were predominantly male (79%), White (68%), non-Hispanic (97%), full professors (50%), and 43% had additional advanced degrees (MPH/PhD/MBA). surgery, anesthesiology and trauma, diseases and pathophysiology of the visual system, and bioengineering, technology, and surgical sciences were the most common study sections that reviewed funded grants to surgeon-scientists. Ninety-two surgeons both received grant funding and served on study section. Study sections with higher surgeon representation were more likely to fund surgeon-scientists ( P < 0.001). Conclusions: Surgeon representation on NIH study sections is strongly associated with receipt of funding by surgeon-scientists. Increasing NIH study section representation by surgeons may help to preserve the surgeon-scientist phenotype. Abstract : Supplemental Digital Content is available in the text